"Narcissism 2.0! Would narcissists follow fellow narcissists on Instagram?" the mediating effects of narcissists personality similarity and envy, and the moderating effects of popularity. (April 2018) - Jin, Seunga Venus; Muqaddam, Aziz
Abstract: Posting selfies is a popular activity that exemplifies self-promotion. Experiment 1 ( N = 116), a 2 (viewers' narcissism: narcissist vs. non-narcissist) x 4 (posts: selfies vs. groupies vs. photos taken by others vs. neutral) between-subjects factorial design, tested effects of viewers' narcissism and Instagram post sources' differential levels of narcissism manifested by different photos. Experiment 2 ( N = 160), a 2 (posts: selfies vs. neutral) x 2 (post source: popular vs. unpopular) x 2 (viewers' need for popularity [NfP]: high vs. low) between-subjects factorial design, examined effects of the source's popularity and viewers' need for popularity. Results of Experiment 1 show selfies and groupies are interpreted as more negatively narcissistic than photos taken by other and neutral photos. Perceived similarity between the Instagram post source and the viewer mediates the causal effects of Instagram post types on attitude toward taking selfies, intention to take selfies, and intention to follow the Instagram post source. Results of Experiment 2 indicate that the post source's popularity and viewers' need for popularity interact to moderate the causal effect of post types on perceived narcissism. Envy mediates the causal effects of the post source's popularity on attitude toward taking selfies, intention to take selfies, and intention to follow the post source. Highlights: Experiment 1 examined effects of viewers' narcissism and posters' photo types. Experiment 2 examined effects of posters' popularity and viewers' need for popularity. Narcissistic similarity mediates post effects on selfie-taking/source-following intentions. Envy mediates popularity effects on selfie-taking/source-following intentions. Sources' popularity and viewers' NfP moderate post effects on perceived narcissism.